Local Economic Development Through Thematic Village Development Guava Crystal Wates Village - Ulis Syifa Ni'mah; Fanisa Zahra Salsabila; Hesti Istikomah; Dhaysaq Hadyalbarr; Selly Aisya Reta (Mustard Journal De Ecobusin, 2024)
This article discusses local economic development as an important strategy in improve the welfare of the community at the village and sub-district levels. This article discusses development of Kampung Jambu Kristal in Wates Subdistrict as an effort to strengthen the local economy. Through a participatory approach, this village utilizes agricultural potential Crystal guava as a superior commodity. The development program includes increasing capacity farmer, optimization production, as well as strategy marketing innovative Which integrated with local tourism. As a result, the development of Kampung Jambu Kristal has contributed positive in create field Work, increase income public, and support local economic resilience in Wates Village. This study is expected to be a model for development economy based on potential local in area other.